Academic Stress and Resilience as Predictors of Pro-Social Behaviour among Undergraduates of Adekunle Ajasin University Akungba-Akoko - Afolabi, Olukayode A.; Balogun, Anthony G.; Adejugbe, Adebola E.; Uye, Emmanuel E. (Happiness: Journal of Psychology and Islamic Science, 2024)
The problems of pro-social behavior among individuals have been in existence from the recorded history. Studies that have investigated pro-social behavior have used different predictors and populations with varied results. Therefore, this study investigated academic stress and resilience as predictors of pro-social behavior among first year undergraduates of Adekunle Ajasin University, Akungba-Akoko, Ondo State, Nigeria. The study adopted cross-sectional survey design while convenience sampling technique was used to collect data from 219 participants using the Pro-social Behavior Scale, Maslach Burnout Inventory and Resilience Scale. Data collected were analyzed using multiple regressions to test three hypotheses which were accepted at a p < .05 level of significance. The result showed that academic stress and resilience jointly predicted pro-social behavior among study participants [R2 =.10, F (2,216) =11.88, p < .05]. In addition, academic stress (β= -.26, p < .05) independently predicted pro-social behavior while resilience did not independently predict pro-social behavior among study participants (β = .12, p > .05). The study concluded that academic stress is a strong predictor of pro-social behavior among study participants. It is recommended that university management and other stakeholders should organize regular seminars on stress reduction techniques that would encourage activities that would lead to pro-social behavior among undergraduates.